2020
DOI: 10.1371/journal.pone.0229119
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetron lucayanum: How many species are valid?

Abstract: The cephalochordates amphioxus or lancelets are benthic marine animals representing the earliest divergent evolutionary lineage within chordates. Although amphioxus are present in most of the world's tropical and temperate oceans, only about thirty different species grouped into three different genera, Branchiostoma, Epigonichthys and Asymmetron have been described. In the genus Asymmetron, only two species have been characterized, although for one of them, A. lucayanum, several cryptic lineages exist. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 23 publications
4
13
0
2
Order By: Relevance
“…Due to this phylogenetic position and their slow evolutionary rate (Louis et al, 2012), lancelets are considered valuable proxies for the chordate ancestor, both at the anatomic and genomic levels (Bertrand and Escrivá, 2011;Holland, 2015). The subphylum Cephalochordata is subdivided into three genera: Branchiostoma, Epigonichthys, and Asymmetron (Poss and Boschung, 1996;Nishikawa, 2004;Zhang et al, 2006;Kon et al, 2007;Holland and Holland, 2010;Yue et al, 2014;Carvalho et al, 2017b;Subirana et al, 2020). Recent analyses of mitochondrial genomes suggested that the genus Asymmetron occupies the basal position and diverged from the Epigonichthys/Branchiostoma clade about 258-171 mya (million years ago) (Subirana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to this phylogenetic position and their slow evolutionary rate (Louis et al, 2012), lancelets are considered valuable proxies for the chordate ancestor, both at the anatomic and genomic levels (Bertrand and Escrivá, 2011;Holland, 2015). The subphylum Cephalochordata is subdivided into three genera: Branchiostoma, Epigonichthys, and Asymmetron (Poss and Boschung, 1996;Nishikawa, 2004;Zhang et al, 2006;Kon et al, 2007;Holland and Holland, 2010;Yue et al, 2014;Carvalho et al, 2017b;Subirana et al, 2020). Recent analyses of mitochondrial genomes suggested that the genus Asymmetron occupies the basal position and diverged from the Epigonichthys/Branchiostoma clade about 258-171 mya (million years ago) (Subirana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the general importance of Branchiostomatidae, little is known about much of this family. Several species were newly described, or their taxonomy has been clarified only recently [2,29,30], and species misidentification or cryptic diversity have been found using molecular approaches or integrative taxonomy [14,[31][32][33][34][35][36]. Moreover, new records of lancelet larvae or adults improved our assessment of species-specific geographical distribution and ecological traits at a range of scales [37][38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Branchiostoma, Epigonichthys and Asymmetron [4][5][6][7][8][9][10][11]. Recent analyses of mitochondrial genomes suggested that the genus Asymmetron occupies the basal position and diverged from the Epigonichthys plus Branchiostoma clade about 42…”
Section: Introductionmentioning
confidence: 99%
“…The subphylum Cephalochordata is subdivided into three genera: Branchiostoma , Epigonichthys and Asymmetron (Poss and Boschung, 1996; Nishikawa, 2004; Zhang et al, 2006; Kon et al, 2007; Holland and Holland, 2010; Yue et al, 2014; Carvalho et al, 2017b; Subirana et al, 2020). Recent analyses of mitochondrial genomes suggested that the genus Asymmetron occupies the basal position and diverged from the Epigonichthys / Branchiostoma clade about 258-171 Mya (million years ago) (Subirana et al, 2020). It was further proposed that the split of the Epigonichthys and Branchiostoma lineages occurred about 182-120 Mya and that speciation within the genus Branchiostoma , between B. belcheri and B. japonicum versus B. floridae and B. lanceolatum , took place about 130-85 Mya (Subirana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation